Data collection: Actionable research to inform rehabilitation and rebuilding of livelihoods in conflict-affected communities in Ethiopia - International Food Policy Research Institute (International Food Policy Research Institute, 2024)
Over the last two decades, Ethiopia achieved rapid and substantial economic growth and development and maintained relative stability within the volatile Horn of Africa region. However, more recently, Ethiopia continue to face major challenges arising from internal conflicts and related shocks. A recent conflict that broke out in November 2020 in Tigray resulted in major displacement and loss of life. The war quickly spelled over to neighboring regions in northern Ethiopia (including Afar and Amhara).[1] These armed conflicts and related shocks have resulted in over 4.4 million internally displaced people (IDPs), and over 21 million individuals require humanitarian assistance (OCHA, 2024). However, widespread conflict persists in other parts of the country, particularly in the Amhara and Oromia regions. Figure 1 illustrates the distribution of different types of conflict events before and after the war broke out in Tigray. While protests and riots were dominant conflict events in the period preceding the first-round survey, battles appear to dominate those conflict events in the three years preceding the second-round survey.